Organizational climate as a predictor of job satisfaction among the staff of educational institutions - Ramjauny, Badiuzzaman Irfaan Zulqarnain; Condori Ramos, Santos Paz; Ramírez Calderón, Dina Lisbeth (Journal of Management and Business Education, 2025)
The objective of the research is to demonstrate organizational climate as a predictor of satisfaction in four institutional educations. The methodology is based on a quantitative, non-experimental, transversal and descriptive-correlational design. A survey was administered to 128 staff members. Results revealed a significant correlation between organizational climate and job satisfaction, with a Spearman’s rho of 0.617, indicating a moderate to strong positive correlation. Notably, the pressure dimension did not significantly correlate with job satisfaction. This research contributes to understanding how specific elements of organizational climate affect staff satisfaction, providing empirical evidence for educational policy and leadership improvements.